The Quest for National Integration in Nigeria: The Federal Character Principle Revisited - Lambert Chidi Nwachukwu; Hakeem Olatunji Tijani (Covenant University Journal of Politics and International Affairs, 2024)
The federal character principle has remained one of the most sensitive issues in Nigeria starting from the late seventies. This is because it has become a necessary factor to Nigeria’s federal practice, as it has been applied in the composition and operation of virtually every public concern like the civil service, the armed forces, education, government appointments, party politics, etc. After about four decades of the introduction of the federal character principle, this paper re-visits the principle vis-à-vis Nigeria’s quest for national integration. In doing this, the paper relied substantially on secondary method of data collection and content analysis. The core assumptions of the Social Justice Theory as developed by John Rawls (1971), were appropriated for the study. The paper finds out that the implementation of the federal character principle has come with a good deal of commendations, controversies, rancour, misgivings and criticisms over the years. The paper argues that as long as Nigeria remains a federation with diversities, the need to balance these diverse interests in the country will always be there. The federal character principle as the normative expression of the equal rights of Nigerians to participate in the affairs of the country was therefore formulated to take care of these differing interests. What is therefore required is to continue to find ways and means of making the principle acceptable to all and sundry by dealing with the rancour, ill-feelings, misgivings and problems that come with its implementation so as to bring about the needed unity and national integration. The paper accordingly made some recommendations in this regard.